Analisis Finansial dan Risiko Usahatani Jeruk Siam di Kecamatan Gunuang Omeh Kabupaten Lima Puluh Kota - Shindy Kurnia Putri; Fembriarti Erry Prasmatiwi; Adia Nugraha (Journal of Food System & Agribusiness, 2022)
This study aims to analyze the financial, sensitivity, and risk of Siamese oranges. The research method uses a survey method. The research locations in the villages of Koto Tinggi and Pandam Gadang, Gunuang Omeh Sub District, Lima Puluh Kota Regency in March to August 2021. Respondents were 32 Siamese orange farmers. Financial data were analyzed using Gross B-C, Net Present Value (NPV), Net B-C, Internal Rate of Return (IRR), and Payback Period (PP). Risk analysis using the Coefficient of Variance (CV). The results showed that Siamese citrus farming was financially feasible with a Gross BC value of 2.62, Net BC 5.55,IRR 0.40, NPV Rp 2.191.191.334,64, PP 5,47 years. Siamese citrus farming is sensitive to a 30% decrease in selling price and 20% production, while a 4.45% increase in costs is not sensitive. The risk shows a CV value of 0.14, risk mitigation by farmers by planting quality seeds, land sanitation, improving cultivation methods, using pesticides and fertilizers according to doses.